Role of Corporate Governance in Corporate Social Responsibility: Mediating Role of Organizational Performance (KASBIT Business Journal, 2020)
The foremost motive of this study is to explore the role of corporate governance on corporate social responsibility through the mediating the role of firm performance in Pakistan. This theoretical and empirical study has examined companies listed in Pakistan Stock Exchange (PSX) from 2015 to 2019 using Slack Resource and Good Management Theory. The dimensions of corporate governance consist of board size, executive directors, non-executive directors, and women directors. Return on Asset (ROA) has been used to measure firm performance. The data collected from (PSX) listed companies critically examines the role of selected variables. Baron and Kenny's (1986) technique is used to evaluate the mediating effect which as a result demonstrated that organizational performance has no mediation between corporate governance dimensions and corporate social responsibility. However, all the dimensions of Corporate Governance have a significant direct impact on ROA and CSR. Results also indicate that ROA and CSR have a positive relationship with each other.
Keywords: Corporate Governance; Corporate social responsibility; firm performance; Slack Resource Theory; Good Management Theory.